Architecture from 'Les Cinq ports militaires de la France'. - Auteur inconnu... (The British Library, 1894)
Notice issue d Europeana. This image has been taken from scan 000115 from "Les Cinq ports militaires de la France". The title and subject terms of this image have been generated from tags, created by users of the British Library's flickr photostream.
Droits : http://creativecommons.org/publicdomain/mark/1.0/
Keywords: europeana; image; patrimoine europeen; Bibliothèque numerique; iconographie; Iconographie